Economic future of Europe: preliminary papers of the second conference of Wastminster 1954 organized by the European movement (London, 1954)
The aim of this introductory report is to analyse the development which took place in international trade just after the second World War and to set out the basic facts of the problems which we have to solve if we want to work towards the gradual restoration of a world market.
Keywords: Economics - Europe